Molecular mechanisms of zooplanktonic toxicity in the okadaic acid-producing dinoflagellate Prorocentrum lima. (15th June 2021) - Gong, Yufeng; Zhang, Keke; Geng, Ningbo; Wu, Minghuo; Yi, Xianliang; Liu, Renyan; Challis, Jonathan K.; Codling, Garry; Xu, Elvis Genbo; Giesy, John P.
Abstract: Prorocentrum lima is a dinoflagellate that forms hazardous blooms and produces okadaic acid (OA), leading to adverse environmental consequences associated with the declines of zooplankton populations. However, little is known about the toxic effects and molecular mechanisms of P. lima or OA on zooplankton. Here, their toxic effects were investigated using the brine shrimp Artemia salina . Acute exposure of A. salina to P. lima resulted in lethality at concentrations 100-fold lower than densities observed during blooms. The first comprehensive results from global transcriptomic and metabolomic analyses in A. salina showed up-regulated mRNA expression of antioxidant enzymes and reduced non-enzyme antioxidants, indicating general detoxification responses to oxidative stress after exposure to P. lima . The significantly up-regulated mRNA expression of proteasome, spliceosome, and ribosome, as well as the increased fatty acid oxidation and oxidative phosphorylation suggested the proteolysis of damaged proteins and induction of energy expenditure. Exposure to OA increased catabolism of chitin, which may further disrupt the molting and reproduction activities of A. salina . Our data shed new insights on the molecular responses and toxicity mechanisms of A. salina to P. lima or OA. The simple zooplankton model integrated with omic methods provides a sensitive assessment approach for studying hazardous algae. Graphical abstract: Image 1 Highlights: P. lima caused lethal effects to A. salina at environmentally realistic densities. P. lima induced oxidative stress and triggered detoxification responses of A. salina . Clearance and repair of damaged proteins and expenditure of energy were enhanced in A. salina exposed to P. lima . OA induced catabolism of chitin in A. salina, resulting in disruption of molting and reproduction process. Abstract : Capsule: This study highlights the importance of utilizing zooplankton and integrated omics techniques for characterizing the toxic effects of algal blooms.